2022
DOI: 10.3390/geosciences12100367
|View full text |Cite
|
Sign up to set email alerts
|

Soil Loss Potential Assessment for Natural and Post-Fire Conditions in Evia Island, Greece

Abstract: A devastating forest fire in August 2021 burned about 517 km2 of the northern part of Evia Island, affecting vegetation, soil properties, sediment delivery and the hydrological response of the catchments. This study focuses on the estimation of the annual soil loss in the study area under natural (pre-fire) and post-fire conditions. The assessment of the soil loss potential was conducted with the application of the Universal Soil Loss Equation (USLE), which is an empirical equation and an efficient way to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The burnt areas were more susceptible to erosion events than the surrounding non-burnt areas [21]. Valkanou et al [22] demonstrated a significant post-fire change in mean annual soil loss that corresponded to an increase of 114% compared to the pre-fire natural conditions. The dominant landcover types ravaged by the wildfires were mostly coniferous woodland (31%), mixed-and broad-leaved forest (21.30%), and to a lesser extent, agroforestry land [20,22,25,26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The burnt areas were more susceptible to erosion events than the surrounding non-burnt areas [21]. Valkanou et al [22] demonstrated a significant post-fire change in mean annual soil loss that corresponded to an increase of 114% compared to the pre-fire natural conditions. The dominant landcover types ravaged by the wildfires were mostly coniferous woodland (31%), mixed-and broad-leaved forest (21.30%), and to a lesser extent, agroforestry land [20,22,25,26].…”
Section: Resultsmentioning
confidence: 99%
“…The main geological outcroppings in the study area are peridotites and mafic volcanic rocks, covered by extensive Neogene deposits [20]. Alluvial deposits occur along the drainage networks' major channels and at the mouths of the rivers [22]. The primary landcover categories heavily impacted by the wildfires included predominantly coniferous woodlands, a blend of mixed and broad-leaved forests, and to a lesser degree, areas designated for agroforestry practices.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that land cover changes can alter soil type distribution, which is mainly attributable to policy orientation and economic development trends [58,59]. For example, the large-scale conversion of cropland to construction land in Tongzhou District has led to significant changes in the distribution of Cinnamon soil and Aeolian soil.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in the post-fire environment, a few months after the fire, highlight significant differences between the values of the chemical parameters in the three analyzed zones (rooting, control, and ring). In the literature, it is well established that wildfires have an impact on the chemical properties of soils, especially in Mediterranean ecosystems [40][41][42]. Many studies indicate a substantial increase in nutrients immediately after a fire event [41,[43][44][45][46], caused by the combustion of vegetation and debris, which significantly affects their availability.…”
Section: Discussionmentioning
confidence: 99%